Harnessing copper-palladium alloy tetrapod nanoparticle-induced pro-survival autophagy for optimized photothermal therapy of drug-resistant cancer. Issue 1 (December 2018) - Zhang, Yunjiao; Sha, Rui; Zhang, Lan; Zhang, Wenbin; Jin, Peipei; Xu, Weiguo; Ding, Jianxun; Lin, Jun; Qian, Jing; Yao, Guangyu; Zhang, Rui; Luo, Fanchen; et al.
Abstract Chemo-PTT, which combines chemotherapy with photothermal therapy, offers a viable approach for the complete tumor eradication but would likely fail in drug-resistant situations if conventional chemotherapeutic agents are used. Here we show that a type of copper (Cu)-palladium (Pd) alloy tetrapod nanoparticles (TNP-1) presents an ideal solution to the chemo-PTT challenges. TNP-1 exhibit superior near-infrared photothermal conversion efficiency, thanks to their special sharp-tip structure, and induce pro-survival autophagy in a shape- and composition-dependent manner. Inhibition of autophagy with 3-methyl adenine or chloroquine has a remarkable synergistic effect on TNP-1-mediated PTT in triple-negative (4T1), drug-resistant (MCF7/MDR) and patient-derived breast cancer models, achieving a level of efficacy unattainable with TNP-2, the identically-shaped CuPd nanoparticles that have a higher photothermal conversion efficiency but no autophagy-inducing activity. Our results provide a proof-of-concept for a chemo-PTT strategy, which utilizes autophagy inhibitors instead of traditional chemotherapeutic agents and is particularly useful for eradicating drug-resistant cancer. "Conventional chemotherapy-photothermal therapy combination has limited efficacy in drug resistant cancers. Here they develop Copper-palladium tetrapod nanoparticles to overcome these challenges and show them to work in synergy with autophagy inhibitors to treat drug resistant cancers"